CTLA-4 blockade in the treatment of colorectal cancer with microsatellite instability - Diana Russo; Francisco Mendes (Iranian Journal of Colorectal Research, 2021)
Context: Colorectal cancer is one of the most common tumours worldwide, with around 10-15% of these related to microsatellite instability which is, in turn, responsible for a high neoantigen load and subsequent high tumour mutational burden. These characteristics are responsible for the poor response of these tumours to chemotherapy, highlighting the need for a different approach in the treatment of patients with microsatellite unstable colorectal cancer. Immunotherapy was proven important in the treatment of these patients, with immune checkpoint inhibition such as CTLA-4 blockade being one of the most promising targets so far. Evidence Acquisition: A PubMed search was done on February 2021 where the used query obtained a total of 33 articles. After the inclusion and exclusion criteria, a total of 21 articles were obtained and used in this narrative review. Results: Several studies with microsatellite unstable colorectal tumours have been done in order to evaluate the advantages and adverse events of CTLA-4 blockade in these patients. Studies show a benefit regarding the progression-free survival, overall survival and overall response rates in patients receiving ipilimumab (anti-CTLA-4) when compared to those who weren’t. Besides, the main adverse events are manageable and are more tolerable than those observed with chemotherapy. Nonetheless, unlike PD-1 blockade, anti-CTLA-4 drugs are currently only approved for the use as a combination therapy in microsatellite unstable colorectal cancer, still awaiting approval as a monotherapy. Conclusion: Microsatellite unstable colorectal tumours deserve a different treatment path, as their characteristics make these tumours poor responders to chemotherapy while at the same time great candidates for immunotherapy, namely with CTLA-4 inhibitors. KEY-WORDS Colorectal cancer; CTLA-4; Immune checkpoint; Immunotherapy; Ipilimumab; Microsatellite instability